A new unique leafhopper genus of Erythroneurini from China, with the description of one new species (Hemiptera, Cicadellidae, Typhlocybinae) - Song, Yuehua; Yuan, Xiaojuan; Tan, Yusha; Webb, Mick D.; Mera, Diana R. (Zootaxa, 2025)
A new genus of the leafhopper tribe Erythroneurini (Cicadellidae, Typhlocybinae) from Huajiang, Guizhou Prov., China, Guizhoura gen. nov., and a new species Guizhoura huajianga sp. nov., are described and illustrated. Detailed morphological descriptions and illustrations of the new genus and new species are provided.